2024
DOI: 10.1186/s12891-024-07331-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the incidence and risk factors of blood transfusion in total knee revision: a retrospective nationwide inpatient sample database study

Xiaoyin Li,
Hao Xie,
Shuxia Liu
et al.

Abstract: Objective This study sought to determine the incidence and risk factors of blood transfusion among patients undergoing total knee revision (TKR) using a nationwide database. Methods A retrospective data analysis was conducted based on the Nationwide Inpatient Sample (NIS), enrolling patients who underwent TKR from 2010 to 2019 with complete information. The patients were divided into two groups based on whether they received blood transfusion or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
0
0
Order By: Relevance
“…In addition, we observed that blood transfusion was associated with an increased risk of developing PPCs (OR = 1.62), especially pneumonia (OR = 1.91) and PE (OR = 1.44). One plausible explanation is that blood transfusion may indicate a disturbance of the patient's circulatory system during the perioperative period, such as anemia, hypotension and even heart failure [34][35][36]. Patients with these circulatory disorders may face a higher risk of developing PPCs after THAR surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we observed that blood transfusion was associated with an increased risk of developing PPCs (OR = 1.62), especially pneumonia (OR = 1.91) and PE (OR = 1.44). One plausible explanation is that blood transfusion may indicate a disturbance of the patient's circulatory system during the perioperative period, such as anemia, hypotension and even heart failure [34][35][36]. Patients with these circulatory disorders may face a higher risk of developing PPCs after THAR surgery.…”
Section: Discussionmentioning
confidence: 99%